GROUNDWATER POTENTIAL AND OVERBURDEN PROTECTIVE CAPACITY IN MAGAMA GUMAU, TORO NORTHEASTERN NIGERIA - BULUS, J. A.; ALUWONG, K. C. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
The study area is underlain by crystalline rocks of the north-eastern part of Nigerian Basement Complex. A geophysical study of electrical resistivity was carried out with the aim of assessing the groundwater potential for alternate water source due to insufficient surface water and low yield boreholes in the area. Thirty-two (32) Vertical Electrical Soundings (VES) were obtained from Magama Gumau and its environs using Schlumberger electrode configuration with current electrode separation (AB) varying from 1.5 to 125 m. The acquired field data were interpreted and iterated using “IX1D” software. The total transverse resistance value (194.75 - 143014 Ωm2) was adopted in the classification of the area into poor, weak, moderate and very good transmissivity zones. The groundwater potential of Magama Gumau is classified into low, medium and high groundwater potential zones based on the integration of geo-electric and Dar- Zarrouk parameters. The VES data indicate three (3) to four (4) geo-electric layers namely: topsoil, clayey soil, fractured basement and fresh basement. The Overburden comprises topsoil, clay/laterite, and fractured basement with thickness ranging from 1.2 to 41.6 m. The zones with overburden thickness of 20 m and above are feasible for groundwater abstraction and constitute about 34.38 % of the area. The aquifer protective capacity of the area was classified into good (> 0.7 mhos), moderate (0.2 – 0.69 mhos), weak (0.1 – 0.19 mhos), and poor (< 0.1 mhos), based on the longitudinal conductance value (0.009036 - 3.771312 mhos). Hence, the result of this work will form the tools for groundwater development, management and infrastructural/structural development planning of Magama Gumau, Toro northeastern Nigeria. Keywords: